PENAAKULAN MORAL DALAM PANTUN PAK NAZEL 101 PERKARA - Syahadah Yusof, Syahidatul; Jamian, Muhd Norizam (JURNAL MELAYU SEDUNIA, 2020)
Pantun is a genre in traditional poetry which represents the traditional Malay literary greatness. Besides having high aesthetic value, pantun also plays a role in conveying advice, education and teaching including moral elements. In this regard, this paper discusses the moral elements contained in the Malay pantun from the perspective of moral reasoning. The data of this study involves 1045 poems contained in the Pantun Pak Nazel 101 Perkara by Nazel Hashim Mohammad (2012). The objective of this paper is to identify and analyse the moral element contained in Malay pantun. The research methodology involves a qualitative approach that includes two methods, namely library research and content analysis. Library research is conducted to obtain information related to the concept of moral reasoning from various reference sources such as journal papers, thesis and scholarly books. Content analysis was conducted on the Pantun Pak Nazel 101 Perkara through intensive reading techniques, interpretation and analysis based on the perspective of moral reasoning. The results of the study found that the element of moral reasoning contained in the book can be analysed based on four elements, namely rational, optimistic, normative and wise thinking. As a result, pantun is an oral tradition heritage that symbolizes the wisdom of the Malays. Pantun became a platform to convey sarcasm, praise, advice, jokes, love and almost every aspect of life including moral elements.